Smart Mom for Disaster Preparedness: Pengasuhan Resilien dalam Meningkatkan Kesadaran Bencana Anak Usia Dini - Sari, Novita; Susanti, Lis; Erlangga, Maulana Deni; Fadilah, Fadilah; Mariam, Mariam; Komariyah, Komariyah; Hulaela, Hulaela; Rosdiana, Rosdiana; Nurjanah, Nurjanah; Sabrina, Annisa; Hikmatullah, Hikmatullah (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This Community Service Program (PKM) aims to improve the understanding and capacity of parents, especially mothers, in implementing resilient parenting as a strategy to build disaster awareness in early childhood. The activity entitled "Smart Mom for Disaster Preparedness" was carried out in Kasemen District, Serang City in an area that is classified as disaster-prone through a qualitative participatory approach with the Focus Group Discussion (FGD) method. Participants in the activity consisted of mothers, PAUD teachers, and partner school principals. The material provided focused on the importance of effective communication based on love languages to strengthen the emotional relationship between mother and child as the basis for children's psychological resilience in facing emergency situations. The results of the FGD showed an increase in participants' understanding of the concept of resilient parenting and the emergence of new awareness regarding the strategic role of families in disaster mitigation education. Participants also began to apply a more empathetic and reflective communication approach in daily parenting. This activity proves that community-based education with a participatory approach can be an effective strategy in building disaster preparedness from an early age, starting from the family circle.